Combined Direct and Indirect Revascularization for Adults with Moyamoya Disease: A Single-Center Retrospective Study - Ayyad, Ali; Al-Salihi, Mohammed Maan; Ahmed, Alaaeldin; Hajali, Amro Al; Hammadi, Firas; Horn, Peter (Asian Journal of Neurosurgery, 2024)
Background Moyamoya vasculopathy is a rare neurological disease characterized by the progressive constriction of major intracranial vessels and secondary collateral formation. In the past decade, the popularity of combined bypass surgery has increased. They take advantage of the quick perfusion of direct bypass and collaterals ingrowth from indirect bypass.Objective This study aimed to describe a single-center experience with surgical management of moyamoya disease (MMD) and moyamoya syndrome (MMS) over 7 years.Materials and Methods In this retrospective medical records review, we enrolled patients diagnosed with MMD and MMS who were treated with combined surgical revascularization at the Hamad Medical Corporation center between 2015 and 2022. SPSS 26.0 was used to analyze the data.Results A total of 20 patients were included, with 15% having MMS. The mean age was 37.4 ± 10.26 years, and 60% of them were males. The mean follow-up period was 13.6 months. The modified Rankin score was significantly decreased by 1.9 ± 2.1, p = 0.0001. Following surgery, no deficits were observed in 16 cases, whereas three were not improved, and one died. Following up on the stroke status, one patient developed a hemorrhagic stroke, and another showed right-side numbness. The postoperative status was substantially linked with the initial clinical presentation (p = 0.004).Conclusion Combined direct and indirect surgical revascularization procedures have favorable outcomes in MMD and MMS patients. Additional rigorous, prospective, controlled, high-quality trials with large-sample are needed to support our results.
Keywords: moyamoya; direct bypass; indirect bypass; combined; revascularization